Pop Up Cafe as a Creative Generator in Jakarta - Prawata, Albertus (Bina Nusantara University, 2015)
The government has a strong role to make plans and shape the city. The planning establishment by the government is based on capital-intensive strategic actions, so they can shape the urban spaces according to acertain set of values. These values are made clearly in the patterns of resource consumption. However, they often create a hierarchical gap between the people and the communities. In the city, the economy becomes the basis of how the urban spaces are shaped and created. New economic activities often have the impact in degrading the quality of the spaces. As a result, the city will lose its attractions, and people feel alienated and they become aesthetically unpleasant. The purpose of this paper is to discuss the interaction and appreciation of creative users and the citizens of the city towards the urban spaces, and how they will encourage endless collaboration amongst local citizens to create thoughtful and meaningful designs for the public. The discussion and arguments will be based on some creative activities such as pop up café/store. It has the importance to be a creative generator and become the urban fabric that support the city and be a part of the sustainable cityconcept. The engagement and ideas from the creative activities can be a strong foundation of a good urban space, that have the power to re-shape the city spaces to be more livable. Therefore, it can also bring a new identity and vibrant atmosphere to a certain area as well as to the city.